The Design of Automatic Clothesline Prototype Based On Arduino Mega 2560 - Arjitya, Faizal Muchlis; , Ir. Bambang Hari Purwoto, MT (2017)
Global warming that currently happens in Indonesia, is causing the change of seasons becomes not stabilized. It makes between dry season and rainy season were could not be predicted anymore. No wonder, in the dry season, the rain could fall suddenly. This condition would distressing when it comes to drying up the clothes. The concern increased when the house is empty, while the wet clothes still at the outside. So, the clothes that were hanged on, could not dry up as well, and at worst they could become dirtier then caused a not-good-smell. To solve the problems, was made a design of automatic clothesline that based on arduino mega 2560. This automatic clothesline works when the LDR censor, raindrop censor, and wire censor could predict the change of seasons around. And the result of those censors is processed by arduino mega 2560, which is used to pull off and pull out the clothesline using the DC motor. Arduino mega 2560 also works as a censor processor to enable the alternatives heater, such as that heater and a fan which is used when the clothes still wet. Otherwise, if the clothes are already dried, the buzzer will active automatically according to data that showed on LCD.